Spletne zbirke SEM - Sosič, Barbara (Etnolog. Nova vrsta (Ljubljana), 2011)
In 2010, the Slovene Ethnographic Museum started providing the users of its website with an online gallery of selected collections of objects and photographs. By the end of the year a total of over 23,000 units were presented online. This number was reached thanks to a several years lasting project of systematic digitisation and conversion of analogue records into digital ones. Its aim was to draw attention to the richness of the museum's collections and data related to them. The presented collections contain extensive knowledge and enable the users to inform themselves on contents that we consider to be important to wider circlers of users.
Keywords: muzeji; Slovene ethnographic museum; muzejske zbirke; collections; museum documentation; Slovenski etnografski muzej; Ljubljana; dostopnsot; muzejska dokumentacija; digitalizacija; digitization; internet; spletne strani; digitalisation